“Remembrance”: Reticence, the Sensual, the Erotic, and the Music for The Irishman - Robynn J. Stilwell (Alphaville: Journal of Film and Screen Media, 2024)
Robbie Robertson’s score for The Irishman (Martin Scorsese, 2019) emphasises the film’s underlying contemplation of impending aging and death. Building on Danijela Kulezic-Wilson’s concepts of reticence, sensuality, and eroticism, this analysis explores the collaborators’ converging stylistic relationship to reticence and proposes a distinction between the “sensual” (an immediate appeal to the senses, residing particularly in timbre, texture, and sonic space) and the “erotic” (a temporal unfolding of anticipation, expectation, evasion, and fulfillment), all concepts richly represented in the score. Two primary cues—the “Theme” that punctuates the narrative at key points and the end-title music, “Remembrance”—share a bluesy aesthetic, but break through the style’s predictable responsorial, circular forms: the “Theme” takes a minimalist approach, the erratic phrasing of its tenuous texture thwarting expectation and building suspense, even dread; in “Remembrance,” three virtuoso blues guitarists solo individually and yet together, abandoning traditional call-and-response and cutting competition to join into a heterophonic communal lament, peaking in an ecstatic release of grief and a reflective recovery of breath.